Voltage-Gated Proton Channel Hv1 Regulates Neuroinflammation and Dopaminergic Neurodegeneration in Parkinson's Disease Models - Matthew L. Neal; Eric E. Beier; Muhammad M. Hossain; Alexa Boyle; Jiaying Zheng; Chunki Kim; Isha Mhatre-Winters; Long-Jun Wu; Jason R. Richardson (MDPI AG, 2023)
Although the precise mechanisms for neurodegeneration in Parkinson's disease (PD) are unknown, evidence suggests that neuroinflammation is a critical factor in the pathogenic process. Here, we sought to determine whether the voltage-gated proton channel, Hv1 (HVCN1), which is expressed in microglia and regulates NADPH oxidase, is associated with dopaminergic neurodegeneration. We utilized data mining to evaluate the mRNA expression of HVCN1 in the brains of PD patients and controls and uncovered increased expression of the gene encoding Hv1, HVCN1, in the brains of PD patients compared to controls, specifically in male PD patients. In an acute 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP; 4 × 16 mg/kg) mouse model of PD, Hvcn1 gene expression was increased 2-fold in the striatum. MPTP administration to wild-type (WT) mice resulted in a ~65% loss of tyrosine hydroxylase positive neurons (TH+) in the substantia nigra (SN), while a ~39% loss was observed in Hv1 knockout (KO) mice. Comparable neuroprotective effects of Hv1 deficiency were found in a repeated-dose LPS model. Neuroprotection was associated with decreased pro-inflammatory cytokine levels and pro-oxidant factors in both neurotoxicant animal models. These in vivo results were confirmed in primary microglial cultures, with LPS treatment increasing Hvcn1 mRNA levels and Hv1 KO microglia failing to exhibit the LPS-mediated inflammatory response. Conditioned media from Hv1 KO microglia treated with LPS resulted in an attenuated loss of cultured dopamine neuron cell viability compared to WT microglia. Taken together, these data suggest that Hv1 is upregulated and mediates microglial pro-inflammatory cytokine production in parkinsonian models and therefore represents a novel target for neuroprotection.